Sequential Extractions and Toxicity Potential of Trace Metals Absorbed into Airborne Particles in an Urban Atmosphere of Southwestern Nigeria - Emmanuel Gbenga Olumayede; Thompson Faraday Ediagbonya (The Scientific World Journal)
The paper investigates the hypothesis that biotoxicities of trace metals depend not only on the concentration as expressed by the total amount, but also on their geochemical fractions and bioavailability. Airborne particles were collected using SKC Air Check XR 5000 high volume Sampler at a human breathing height of 1.5–2.0 meters, during the dry season months from November 2014 to March 2015 at different locations in Akure (7°10′N and 5°15′E). The geochemical-based sequential extractions were performed on the particles using a series of increasingly stringent solutions selected to extract metals (Cd, Cu, Cr, Ni, Pb, Zn, and Mn) into four operational geochemical phases—exchangeable, reducible, organic, and residual—and then quantified using an Atomic Absorption Spectrophotometer. The results showed metals concentration of order Pb > Cr > Cd > Zn > Ni > Cu > Mn. However, most metals in the samples exist in nonmobile fractions: exchangeable (6.43–16.2%), reducible (32.58–47.39%), organic (4.73–9.88%), and residual (18.28–27.53%). The pollution indices show ingestion as the leading route of metal exposure, with noncarcinogenic (HQ) and cancer risk (HI) for humans in the area being higher than 1.0 × 10−4, indicating a health threat.